New Method for Analyzing the Flutter Stability of Hingeless Blades with Advanced Geometric Configurations in Hovering - Si-wen Wang; Jing-long Han; Quan-long Chen; Hai-wei Yun; Xiao-mao Chen (International Journal of Aerospace Engineering)
A new method used to analyze the aeroelastic stability of a helicopter hingeless blade in hovering has been developed, which is especially suitable for a blade with advanced geometric configuration. This method uses a modified doublet-lattice method (MDLM) and a 3-D finite element (FE) model for building the aeroelastic equation of a blade in hovering. Thereafter, the flutter solution of the equation is calculated by the V-g method, assuming blade motions to be small perturbations about the steady equilibrium deflection. The MDLM, which is suitable to calculate the unsteady aerodynamic force of nonplanar rotor blade in hovering, is developed from the doublet-lattice method (DLM). The structural analysis tool is the commercial software ANSYS. The comparisons of the obtained results against those in the literatures show the capabilities of the MDLM and the method of structural analysis. The flutter stabilities of swept tip blades with different aspect ratios are analyzed using the new method developed in this work and the usual method on the basis of the unsteady strip theory and beam model. It shows that considerable differences appear in the flutter rotational velocities with the decrease of the aspect ratio. The flutter rotational velocities obtained by the present method are evidently lower than those obtained by the usual method.